Current Methods for Inducing Pluripotency in Somatic Cells. (26th March 2013) - Tavernier, Geertrui; Mlody, Barbara; Demeester, Jo; Adjaye, James; De Smedt, Stefaan C.
Abstract The groundbreaking discovery of reprogramming fibroblasts towards pluripotency merely by introducing four transcription factors (OCT4, SOX2, KLF4 and c‐MYC) by means of retroviral transduction has created a promising revolution in the field of regenerative medicine. These so‐called induced pluripotent stem cells (iPSCs) can provide a cell source for disease‐modelling, drug‐screening platforms, and transplantation strategies to treat incurable degenerative diseases, while circumventing the ethical issues and immune rejections associated with the use of non‐autologous embryonic stem cells. The risk of insertional mutagenesis, caused both by the viral and transgene nature of the technique has proven to be the major limitation for iPSCs to be used in a clinical setting. In view of this, a variety of alternative techniques have been developed to induce pluripotency in somatic cells. This review provides an overview on current reprogramming protocols, discusses their pros and cons and future challenges to provide safe and transgene‐free iPSCs.